Control interno a las cuentas por cobrar y su incidencia en la morosidad de la empresa auto1partes, Cantón Santo Domingo, año 2022 - Aragón Olvera , Vanessa Viviana (2024)
This research addresses a vitally important problem of internal control applied to accounts receivable, including the evaluation of credit policies, supervision of compliance with payment terms and collection strategies. This research aims to evaluate the internal control and its impact on accounts receivable delinquency by determining the factors that affect the company's continued growth and success in the market, as well as the positive benefits of maintaining a healthy cash flow and ensuring that its customers comply with payments in a timely manner to subsequently establish strategies to improve and strengthen internal controls in the management of accounts receivable and reduce delinquencies. In this sense, this work was developed in the AUTO1PARTES company in the Santo Domingo canton. Due to this, the study population is made up of the owner manager, accountant, warehouse staff and sales advisors. The research is qualitative, quantitative, field, descriptive and analytical, methods such as analysis, deductive and inductive and observation were used, a survey and an internal control questionnaire were developed, in obtaining data, they were tabulated and analyzed. They examine the internal control systems used by the company to manage accounts receivable and investigate how these systems impact the customer delinquency rate. The study provides recommendations aimed at improving internal procedures and reducing late payment levels in the company.